Advancing Sustainable Development through Education Equity: Cross-Country Economic Evidence - Zheng, Zheyun (Journal of Sustainable Competitive Intelligence, 2025)
Purpose: The study focuses on the ways in which education equity can be employed to stimulate sustainable development between national economies that have interest to China and Thailand. It talks of how equal access to education contributes to human capital and productivity and inclusive economic growth and provides empirical evidence of the same in the light of a cross country comparative framework. Methodology/Approach: The panel data used in the quantitative econometric analysis were 2000-2023, which was gathered in the World Bank, UNESCO, and national statistical bureaus. The identification of the causal relationship between education equity and the outcomes of sustainable development was completed with the help of the fixed-effects regression models as well as the indicators, such as the Education Gini Index, Sustainable development goal (SDG) achievement scores, and GDP per capita growth. Originality/Relevance: The research is based on the discussion of sustainable development and it introduces the equity of education in the macroeconomic analysis as the gap that exists between social justice and the economic sustainability. It pays attention to the contribution of structural educational reform and inclusion in alleviating regional disparities as well as accelerating economic sustainability on a long-term basis in developing economies. Key Findings: The results show that China and Thailand are positively correlated in terms of the education equity and sustainability indices. The rapid rural education has brought about quantifiable benefits in the human capital and environmental consciousness in China and the gender parity programs in Thailand. The marginal effect however is higher in China because it has a wider scope of investment and regional policies of innovation. The results indicate that the key to the attainment of a balanced, sustainable economic development lies in the inclusion of educational structures. Theoretical/Methodological Contributions: The research has added to the literature by incorporating economic modeling and sustainable development theory to provide a model that can be replicated in other countries to analyze educational inclusiveness. It contributes to the empirical knowledge of the functioning of equity in education as a long-term source of sustainability in education, leading the policymakers to